Tourism Communication Strategy in Developing Halal Tourism in The Lake Toba Tourism Area of North Sumatra - Afwan Syahril Manurung; Purbatua Manurung (Universitas Merdeka Malang, 2024)
This research discusses the concept and implementation of halal tourism in the Lake Toba Tourism Area, particularly in Tomok and its surroundings. The research highlights the barriers in implementing the halal tourism concept, especially in non-Muslim majority areas. One of the main obstacles is the fear of losing local wisdom, especially in the area of non-halal culinary, which can trigger local community rejection. However, the research also emphasizes the importance of the halal tourism concept in providing a sense of security and comfort for Muslim tourists, as well as boosting the local economy. The research method involves literature review and data analysis from previous studies, such as Rose Emmaria's research, Kemenparekraf, and other relevant studies. The results show that intensive communication between the government, community, and related parties is key in overcoming resistance to the concept of halal tourism. In addition, clear regulations and involving various parties are also needed to strengthen the implementation of halal tourism.